Pengaruh Hedonic Shopping Motivation, Influencer Marketing Dan Self Control Terhadap Impulsive Buying Pada Mahasiswa Pengguna Tiktok Shop - Dewi BintangSubekti; Muthmainnah Muthmainnah; Erwin S aputraSiregar (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to analyze the effects of hedonic shopping motivation, influencer marketing, and self-control on impulsive buying behavior among 2022 cohort students using TikTok Shop at UIN Sulthan Thaha Saifuddin Jambi from the perspective of Islamic consumer behavior. In Islamic economics, consumption behavior should be guided by the principles of moderation, benefit (maslahah), and self-restraint to avoid excessive consumption (israf) and wasteful spending. This study employed a quantitative approach using a survey method. The sample consisted of 350 respondents selected through proportional stratified random sampling based on predetermined inclusion criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that hedonic shopping motivation, influencer marketing, and self-control have positive and significant effects on impulsive buying, with path coefficients of 0.418, 0.290, and 0.302, respectively, and p-values of 0.000. Simultaneously, these three variables explain 33.1% of the variance in impulsive buying behavior. The measurement model evaluation confirmed that all constructs met the criteria of validity and reliability, while the structural model showed no significant multicollinearity issues. These findings suggest that psychological factors, digital marketing strategies, and self-regulatory capabilities play important roles in shaping impulsive buying behavior on social commerce platforms. From an Islamic consumer behavior perspective, the findings underscore the importance of strengthening moderate, rational, and responsible consumption values to minimize impulsive buying tendencies among university students.